1970
DOI: 10.1111/j.1600-0765.1970.tb00699.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of topical application of chlorhexidine on the bacterial colonization of the teeth and gingiva

Abstract: Six dental students participated in two experiments throughout which they ceased all active oral hygiene measures. In the first experiment a 2 per cent solution of chlorhexidine and in the second a placebo solution was applied topically each day to all teeth. Throughout both 15 day experiments the bacterial colonization of the attached gingiva, gingival margin and tooth surface was examined using impression preparations and a microcolony technique. Bacterial colonization of the tooth surface occurred rapidly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
2

Year Published

1972
1972
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(29 citation statements)
references
References 8 publications
2
25
0
2
Order By: Relevance
“…The results of the preclinical antiplaque agent screening procedure used here were previously demonstrated to be remarkably consistent with those established empirically in assessing the minimal conditions for efficacy of the bisbiguanide chlorhexidine in human clinical trials testing its antiplaque, antigingivitis, and anticaries effects (5,31,45). It is felt that such preclinical screening ofagents against target plaque-forming microorganisms might avoid costly, time-consuming, and potentially hazardous empirical approaches to human clinical trials.…”
Section: Resultsmentioning
confidence: 57%
“…The results of the preclinical antiplaque agent screening procedure used here were previously demonstrated to be remarkably consistent with those established empirically in assessing the minimal conditions for efficacy of the bisbiguanide chlorhexidine in human clinical trials testing its antiplaque, antigingivitis, and anticaries effects (5,31,45). It is felt that such preclinical screening ofagents against target plaque-forming microorganisms might avoid costly, time-consuming, and potentially hazardous empirical approaches to human clinical trials.…”
Section: Resultsmentioning
confidence: 57%
“…These include the C. albicans which causes thrush infection in the mouth, and bacteria that may infect mouth ulcers or other mouth sores, e.g. after dental surgery 5,9,10,14 . The clinical and microbiological efficacy of chlorine dioxide (ClO 2 ) as a topical antiseptic and disinfectant agent also used for the treatment of chronic atrophic candidiasis in geriatric patients has been assessed 25 .…”
Section: Introductionmentioning
confidence: 99%
“…55 Davies et al suggested that locally adsorped chlorhexidine complexed with ions from the oral environment and showed this in vitro with the colour produced between chlorhexidine and food dyes. 56 Following this observation, in vitro and in vivo experiments showed that chlorhexidine and other antiseptics known to cause staining in vivo could bind dietary chromogens to surfaces to produce staining.…”
Section: Extrinsic Discolourationmentioning
confidence: 99%
“…No longer accepted theories of stain formation with chlorhexidine include breakdown of chlorhexidine in the oral cavity to form parachloraniline 54 and also that chlorhexidine may reduce bacterial activity such that partly metabolised sugars were broken down and then degraded over time to produce brown-coloured compounds. 55 Most recent debate has centred around three possible mechanisms. 7 Non-enzymatic browning reactions: Berk suggested that the protein and carbohydrate in the acquired pellicle could undergo a series of condensation and polymerisation reactions leading to discolouration of the acquired pellicle.…”
Section: Extrinsic Discolourationmentioning
confidence: 99%